Aromatic synthetic graphene self-assembled porous carbon material as well as preparation method and application thereof

By using silica aerogel template and aromatic polycondensation reaction to generate graphene self-assembled porous carbon material, the problem of easy stacking of graphene is solved, the specific surface area and conductivity of the material are improved, and the capacitance performance and cycle of supercapacitors are significantly improved. performance.

CN119218980APending Publication Date: 2024-12-31CHINA PETROLEUM & CHEMICAL CORP +1

Patent Information

Application Number
CN202310778500.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-28
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

Graphene is easy to stack in practical applications, resulting in a decrease in its specific surface area and is unable to fully utilize the advantages of supercapacitor electrode materials.

Method used

Silica aerogel is used as a template to generate graphene self-assembled porous carbon material through aromatic polycondensation reaction, breaking the large Π bond interaction between graphene sheet layers, forming a three-dimensional network structure, and combining high-temperature carbonization treatment to improve the material ratio Surface area and conductivity.

Benefits of technology

It effectively solves the problem of easy stacking of graphene, improves the specific surface area and conductivity of the material, significantly improves the capacitance and cycling performance, and is suitable for supercapacitor electrode materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119218980A_ABST
    Figure CN119218980A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of electrode materials, and discloses an arene-synthesized graphene self-assembled porous carbon material and a preparation method and application thereof.The preparation method comprises the steps that 1, in the presence of protective gas, a solvent, a catalyst and optional fused salt, silicon dioxide aerogel serves as a template, arene serves as a reaction monomer, a reaction is conducted, and an arene-synthesized graphene self-assembled porous carbon material is obtained; a graphene self-assembled precursor material is obtained; and (2) carrying out carbonization treatment on the graphene self-assembled precursor material to obtain the arene synthesized graphene self-assembled porous carbon material. Aromatic hydrocarbon is combined with silicon-oxygen bonds on the surface of a silicon dioxide template, interaction of large pi bonds between graphene sheet layers is broken, and the problem that graphene materials are prone to stacking can be effectively solved; the graphene self-assembled porous carbon material prepared by the method is high in specific surface area, high in conductivity and excellent in capacitive performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of electrode materials, and more specifically, to an aromatic hydrocarbon synthesized graphene self-assembled porous carbon material and a preparation method and application thereof. Background Art

[0002] Supercapacitors are green, safe, and efficient energy storage and conversion devices with the advantages of high power density, long cycle life, fast charge and discharge speed, high safety factor, environmental protection, and low cost. They are widely used in new energy vehicles, information and communications, aerospace, national defense science and technology, etc. Electrode materials are the core of supercapacitors and one of the important factors affecting their electrochemical performance.

[0003] In recent years, graphene has attracted great attention due to its high specific surface area (2630m 2 g -1 ), high conductivity and theoretical specific capacitance (550F / g), and is widely used as an electrode material for supercapacitors. However, the strong van der Waals forces between graphene sheets make it easy to stack and aggregate in practical applications, resulting in its actual specific surface area (<500m 2 / g) is much smaller than the theoretical value, and its advantages as a supercapacitor electrode material cannot be fully utilized.

[0004] Therefore, solving the stacking problem of graphene and improving capacitance performance are the goals and directions of graphene electrode materials for supercapacitors. Summary of the invention

[0005] The purpose of the present invention is to provide a kind of aromatic hydrocarbon synthetic graphene self-assembled porous carbon material and its preparation method and application, by using silica aerogel as template, using aromatic hydrocarbon as raw material, polycondensation reaction occurs to generate graphene, and self-assembles into a three-dimensional network structure on the template surface, and further condenses to obtain a kind of graphene self-assembled porous carbon material after high temperature carbonization. And in the present invention, aromatic hydrocarbons are combined with silicon-oxygen bonds on the surface of silica template, breaking the large π bond interaction between graphene sheets, and can effectively solve the problem that graphene materials are easy to stack; The graphene self-assembled porous carbon material prepared by the present invention has a high specific surface area, strong conductivity, and excellent capacitance performance and cycle performance.

[0006] In order to achieve the above object, the first aspect of the present invention provides a method for preparing an aromatic hydrocarbon synthesized graphene self-assembled porous carbon material, the preparation method comprising:

[0007] (1) in the presence of a protective gas, a solvent, a catalyst and an optional molten salt, using a silica aerogel as a template and an aromatic hydrocarbon as a reaction monomer to react to obtain a graphene self-assembly precursor material;

[0008] (2) Carbonizing the graphene self-assembly precursor material to obtain the aromatic hydrocarbon synthesized graphene self-assembly porous carbon material.

[0009] The second aspect of the present invention provides an aromatic hydrocarbon synthesized graphene self-assembled porous carbon material prepared by the above preparation method.

[0010] The third aspect of the present invention provides the use of the above-mentioned aromatic hydrocarbon synthesized graphene self-assembled porous carbon material as a supercapacitor electrode material.

[0011] The technical solution of the present invention has the following beneficial effects:

[0012] In the present invention, the aromatic hydrocarbons are combined with the silicon-oxygen bonds on the surface of the silica template to break the large π-bond interactions between graphene sheets, thereby effectively solving the problem of easy stacking of graphene materials.

[0013] In the present invention, by polycondensing different raw aromatic hydrocarbons into graphene self-assembly module groups of different structural sizes, the pore structure and distribution of the porous material can be regulated, and the porous material with the target pore structure can be designed and prepared.

[0014] In the present invention, the self-assembly precursor material can be further polycondensed after heating to form a stable skeleton structure, and maintain the three-dimensional network structure formed by self-assembly.

[0015] The present invention does not use a complicated HF etching template method, but removes most of the SiO at high temperature. 2 By controlling the temperature, an appropriate amount of silicon heteroatom doping can be retained, which increases the electron density of the material and produces a certain amount of pseudocapacitance during the charge transfer process, thereby increasing the specific capacitance without excessively affecting the cycle performance, thereby achieving the purpose of improving the capacitance performance without affecting the cycle performance.

[0016] The graphene self-assembled porous carbon material prepared by the invention has high specific surface area, strong conductivity and excellent capacitance performance.

[0017] The method of the invention is simple, the conditions are mild and controllable, and it has good industrial application prospects.

[0018] Other features and advantages of the present invention will be described in detail in the following detailed description. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Exemplary embodiments of the present invention will be described in more detail with reference to the accompanying drawings.

[0020] Figure 1 The Fourier infrared spectrum of the aromatic hydrocarbon synthesized graphene self-assembled porous carbon material according to Example 1 of the present invention is shown.

[0021] Figure 2A scanning electron microscope image of the aromatic hydrocarbon synthesized graphene self-assembled porous carbon material according to Example 1 of the present invention is shown.

[0022] Figure 3 The Raman spectrum of the aromatic hydrocarbon synthesized graphene self-assembled porous carbon material according to Example 1 of the present invention is shown, wherein the vertical axis represents the peak intensity, and the horizontal axis represents the wave number of the Raman spectrum.

[0023] Figure 4 The charge and discharge curves of the aromatic hydrocarbon synthesized graphene self-assembled porous carbon material at different current densities according to Example 1 of the present invention are shown.

[0024] Figure 5 The graph shows the cycle performance of the aromatic hydrocarbon synthesized graphene self-assembled porous carbon material according to Example 1 of the present invention, wherein the horizontal axis represents the number of cycles and the vertical axis represents the retention rate. DETAILED DESCRIPTION

[0025] The preferred embodiments of the present invention will be described in more detail below. Although the preferred embodiments of the present invention are described below, it should be understood that the present invention can be implemented in various forms and should not be limited to the embodiments set forth herein.

[0026] The first aspect of the present invention provides a method for preparing an aromatic hydrocarbon synthesized graphene self-assembled porous carbon material, the preparation method comprising:

[0027] (1) in the presence of a protective gas, a solvent, a catalyst and an optional molten salt, using a silica aerogel as a template and an aromatic hydrocarbon as a reaction monomer to react to obtain a graphene self-assembly precursor material;

[0028] (2) Carbonizing the graphene self-assembly precursor material to obtain the aromatic hydrocarbon synthesized graphene self-assembly porous carbon material.

[0029] The preparation method of the present invention uses silica aerogel as a template and aromatic hydrocarbon as a raw material, connects the template with chemical bonds to generate a condensation reaction to generate graphene structural units, and then self-assembles into a three-dimensional network structure, and further condenses after high-temperature carbonization to obtain a graphene self-assembled porous carbon material.

[0030] In the present invention, the silica aerogel contains a large number of pore structures inside, which is an excellent template for graphene to self-assemble into a three-dimensional network structure and prevent stacking.

[0031] In the present invention, preferably, in step (1), after the reaction is completed, the reaction product is dried at 100-120° C. to obtain a graphene self-assembly precursor material.

[0032] According to the present invention, preferably, the catalyst is added in steps, and the stepwise addition is to first add a part of the catalyst, react for a period of time, and then add another part of the catalyst to continue the reaction;

[0033] Preferably, relative to 1 mol of aromatic hydrocarbon, the amount of the catalyst added is 0.25 to 2 mol, preferably 0.5 to 1 mol, and the amount of the other catalyst added is 0.25 to 2 mol, preferably 0.5 to 1 mol;

[0034] Preferably, the reaction time is 1-2 hours, and the reaction time is 1 to 9 hours.

[0035] In the present invention, preferably, when molten salt exists, the molten salt can be added before, after or simultaneously with the catalyst, specifically in one of the following ways: Way 1: Under a protective gas atmosphere, in a mixed system containing a solvent, silica aerogel and aromatic hydrocarbons, first add the molten salt, stir and mix, then add a part of the catalyst, react for a period of time, and finally add another part of the catalyst to continue the reaction; preferably, first add the molten salt, stir and mix for 0.5 to 2 hours, then add a part of the catalyst, react for 1-2 hours, and finally add another part of the catalyst to continue the reaction for 1 to 9 hours.

[0036] Method 2: In a protective gas atmosphere, in a mixed system containing a solvent, silica aerogel and aromatic hydrocarbons, first add a part of the catalyst, react for a period of time, then add another part of the catalyst to react for a period of time, and finally add molten salt to continue the reaction; preferably, first add a part of the catalyst, react for 1-2h, then add another part of the catalyst to react for 1~9h, and finally add molten salt to continue the reaction for 1~9h.

[0037] Method 3: In a protective gas atmosphere, in a mixed system containing a solvent, silica aerogel and aromatic hydrocarbons, first add a portion of the catalyst and molten salt, react for a period of time, and then add another portion of the catalyst to continue the reaction; preferably, first add a portion of the catalyst and molten salt, react for 1-2 hours, and then add another portion of the catalyst to continue the reaction for 1 to 9 hours.

[0038] When the molten salt does not exist, the preparation method of the present invention is preferably: in a protective gas atmosphere, in a mixed system containing a solvent, a silica aerogel and an aromatic hydrocarbon, a portion of the catalyst is first added, reacted for a period of time, and then another portion of the catalyst is added to continue the reaction; preferably, a portion of the catalyst is first added, reacted for 1-2 hours, and then another portion of the catalyst is added to continue the reaction for 1 to 9 hours.

[0039] In the present invention, Lewis acid catalyzes cationic polymerization of aromatic hydrocarbons followed by dehydrogenation cyclization to form a graphene structure. The reaction efficiency is low and it is difficult to obtain a large molecular weight graphene structure. The presence of molten salt can promote the conversion of the reaction, and the degree of polycondensation is higher. Polycondensation is performed on the surface of the template agent silica aerogel to form a graphene self-assembled precursor structure with a larger molecular weight.

[0040] According to the present invention, preferably, the aromatic hydrocarbon is a condensed ring aromatic hydrocarbon, preferably including at least one of naphthalene, biphenylene, methylnaphthalene, phenanthrene, pyrene, fluorene, anthracene, indene, benzopyrene, azulene, tetracene, pentacene, triacene, hexacene and heptabenzocyclopentadiene.

[0041] In the present invention, the above aromatic hydrocarbons contain condensed ring structures, which are structural units for condensation into graphene. Under the action of a catalyst, graphene structures of different structures can be designed and regulated to synthesize, thereby providing structural units for self-assembly into porous materials with different pore structures.

[0042] According to the present invention, preferably, the catalyst is a Lewis acid, preferably at least one of aluminum chloride, trimethylaluminum, aluminum bromide, ferric chloride, boron trichloride, antimony chloride, cupric chloride, cuprous iodide, cuprous bromide, boron trifluoride, tin tetrachloride, titanium tetrachloride and silver trifluoromethanesulfonate;

[0043] The molten salt includes at least one of sodium chloride, sodium nitrate, sodium sulfate, barium chloride, calcium chloride, calcium sulfate, copper chloride, potassium chloride, potassium sulfate and potassium nitrate;

[0044] The solvent includes at least one of dichloroethane, dichloromethane, chloroform, carbon tetrachloride, ethyl acetate and xylene;

[0045] The protective gas is nitrogen.

[0046] In the present invention, the above solvent has good compatibility with the silica aerogel and the raw material aromatic hydrocarbon, which is beneficial to the subsequent self-assembly and polycondensation process on the silica surface.

[0047] According to the present invention, preferably, in step (1), the mass ratio of the silica aerogel to the aromatic hydrocarbon is 1:(2-5);

[0048] The molar ratio of the aromatic hydrocarbon to the catalyst is 1:(0.5-4), preferably 1:(1-2);

[0049] The molar ratio of the molten salt to the aromatic hydrocarbon is (0-3):1, preferably (1.5-2):1;

[0050] The reaction temperature is 30-100°C.

[0051] In the present invention, too little aromatic hydrocarbons cannot fully utilize the large amount of pores and specific surface area inside the silica aerogel, and the efficiency of preparing the product is low; too much aromatic hydrocarbons will self-condense, and a structure with high porosity and high specific surface area cannot be obtained.

[0052] According to the present invention, preferably, in step (2), the carbonization treatment is to heat the graphene self-assembly precursor material to 300-600° C. in a nitrogen atmosphere for carbonization for 1-3 hours, then mix it with an activator, and carbonize it at 600-900° C. for 1-5 hours to obtain a carbonized product;

[0053] Preferably, after the carbonization treatment, the carbonization product is washed with water, ultrasonically treated and dried to obtain the aromatic hydrocarbon synthesized graphene self-assembled porous carbon material;

[0054] Preferably, the mass ratio of the graphene self-assembly precursor material to the activator is 1:(1-3).

[0055] In the present invention, the graphene self-assembly structure in the graphene self-assembly precursor forms a connection at high temperature to obtain a three-dimensional network structure, and under the activation of an activator, more fine micropores are generated, further improving the porosity and specific surface area of ​​the material.

[0056] In the present invention, the molten salt is in liquid form during the high temperature process and flows between graphene sheets to act as a separator, thereby preventing product agglomeration and network structure collapse, so that the graphene self-assembly structure on the surface of the silica template can be maintained, and the diffusion activation of the activator inside the material is promoted, thereby producing a better synergistic effect with the activator on generating more pore structures.

[0057] The second aspect of the present invention provides an aromatic hydrocarbon synthesized graphene self-assembled porous carbon material prepared by the above preparation method.

[0058] According to the present invention, preferably, the aromatic hydrocarbon synthesized graphene self-assembled porous carbon material is a three-dimensional network structure.

[0059] According to the present invention, preferably, the specific surface area of ​​the aromatic hydrocarbon synthesized graphene self-assembled porous carbon material is 1500m 2 / g~2600m 2 / g, and the specific capacitance is 165F / g~353F / g at a current density of 0.05A / g.

[0060] The third aspect of the present invention provides the use of the above-mentioned aromatic hydrocarbon synthesized graphene self-assembled porous carbon material as a supercapacitor electrode material.

[0061] The present invention is further described below by examples:

[0062] In the following embodiments, the test conditions of specific capacitance at a current density of 0.05A / g are as follows: the prepared porous carbon material, carbon black, and polyvinylidene fluoride emulsion are mixed evenly in a mass ratio of 85:10:5 to form an electrode sheet with a thickness of about 0.5mm, which is placed in a vacuum oven at 120 degrees Celsius and dried for 24 hours. The electrode sheets are assembled, and a button-type supercapacitor is prepared using a 6mol / L KOH solution as the electrolyte. The electrochemical performance test is carried out using a blue battery test system at a current density of 0.05A / g;

[0063] In Example 1 Figure 4 The test conditions are as follows: button-type supercapacitors were prepared according to the above method, and the blue battery test system was used to test the supercapacitors under the following different current density conditions: 0.05A / g, 0.1A / g, 0.5A / g, 1A / g, and 2A / g.

[0064] Example 1

[0065] The preparation method of aromatic hydrocarbon synthesized graphene self-assembled porous carbon material is as follows:

[0066] 1. Add 1.4g silica aerogel and 40ml dichloromethane into a flask and stir evenly under nitrogen atmosphere;

[0067] 2. Add 6 g of naphthalene, stir evenly, then add 6 g of aluminum chloride, react at 60 ° C for 1 hour, then add 7.5 g of ferric chloride to react for 5 hours, filter; dry at 120 ° C for 3 hours to obtain a graphene self-assembly precursor material;

[0068] 3. Place 1 g of the above graphene self-assembly precursor material in a tubular furnace, heat it to 500°C at 10°C / min under a nitrogen atmosphere and carbonize it for 1 hour; take it out and mix it with 3 g of KOH, place it at 700°C for carbonization for 1 hour, wash the carbonized product with water, ultrasonically treat it, and dry it to obtain a graphene self-assembled porous carbon material.

[0069] After testing, the specific surface area of ​​the graphene self-assembled porous carbon material in this embodiment is 1879m 2 / g, specific capacitance 165F / g at current density of 0.05A / g.

[0070] like Figure 1 As shown, 3432cm -1 and 1633cm -1 The peak is the OH bond stretching vibration peak, 2922cm -1 The weak stretching vibration peak at 1111cm is the absorption peak of saturated CH bond. -1 The characteristic absorption peak of Si-O bond is 470cm -1 The absorption peak is caused by the bending vibration of Si-O-Si bond.

[0071] like Figure 2 As shown, the graphene self-assembled porous carbon material of this embodiment is a three-dimensional network structure.

[0072] like Figure 3 As shown, the Raman spectrum of the graphene self-assembled porous carbon material of the embodiment, 1350cm -1 D peak, 1600cm -1 G peak of graphene, 2600~2900cm -1 is a 2D peak.

[0073] like Figure 4 As shown, the charge and discharge curves of this embodiment at different current densities have a slightly deformed triangular shape, indicating that the battery has pseudocapacitance caused by the silicon-containing groups in the graphene.

[0074] like Figure 5 As shown, the present embodiment has a cycle performance of 30,000 cycles at a current density of 1 A / g, and a capacity retention rate of more than 90%.

[0075] Example 2

[0076] The preparation method of aromatic hydrocarbon synthesized graphene self-assembled porous carbon material is as follows:

[0077] 1. Add 1.4g silica aerogel and 40ml dichloromethane into a flask and stir evenly under nitrogen atmosphere;

[0078] 2. Add 6 g of naphthalene, stir evenly, then add 6 g of aluminum chloride, react at 60 ° C for 1 hour, then add 7.5 g of ferric chloride to react for 5 hours, filter; dry at 120 ° C for 3 hours to obtain a graphene self-assembly precursor material;

[0079] 3. Place 1 g of the above graphene self-assembly precursor material in a tubular furnace, heat it to 500°C at 10°C / min under a nitrogen atmosphere and carbonize it for 1 hour; take it out and mix it with 3 g of KOH, place it at 900°C for carbonization for 1 hour, wash the carbonized product with water, ultrasonically treat it, and dry it to obtain a graphene self-assembled porous carbon material.

[0080] After testing, the specific surface area of ​​the graphene self-assembled porous carbon material in this embodiment is 2132m 2 / g, specific capacitance 265F / g at current density of 0.05A / g.

[0081] Example 3

[0082] The preparation method of aromatic hydrocarbon synthesized graphene self-assembled porous carbon material is as follows:

[0083] 1. Add 1.4g silica aerogel and 40ml dichloromethane into a flask and stir evenly under nitrogen atmosphere;

[0084] 2. Add 6 g of naphthalene, stir evenly, then add 6 g of aluminum chloride, react at 60 ° C for 1 hour, then add 7.5 g of ferric chloride to react for 5 hours, filter; dry at 120 ° C for 3 hours to obtain a graphene self-assembly precursor material;

[0085] 3. Place 1 g of the above graphene self-assembly precursor material in a tubular furnace, heat it to 500°C at 10°C / min under a nitrogen atmosphere and carbonize it for 1 hour; take it out and mix it with 3 g of KOH, place it at 800°C for carbonization for 1 hour, wash the carbonized product with water, ultrasonically treat it, and dry it to obtain a graphene self-assembled porous carbon material.

[0086] After testing, the specific surface area of ​​the graphene self-assembled porous carbon material in this embodiment is 2476m 2 / g, specific capacitance 318F / g at current density of 0.05A / g.

[0087] Example 4

[0088] The preparation method of aromatic hydrocarbon synthesized graphene self-assembled porous carbon material is as follows:

[0089] 1. Add 1.4g silica aerogel and 40ml dichloromethane into a flask and stir evenly under nitrogen atmosphere;

[0090] 2. Add 6 g of pyrene, stir evenly, then add 4 g of aluminum chloride, react at 60 ° C for 1 h, then add 5 g of ferric chloride and react for 5 h, filter; dry at 120 ° C for 3 h to obtain a graphene self-assembly precursor material;

[0091] 3. Place 1 g of the above graphene self-assembly precursor material in a tubular furnace, heat it to 500°C at 10°C / min under a nitrogen atmosphere and carbonize it for 1 hour; take it out and mix it with 3 g of KOH, place it at 800°C for carbonization for 1 hour, wash the carbonized product with water, ultrasonically treat it, and dry it to obtain a graphene self-assembled porous carbon material.

[0092] After testing, the specific surface area of ​​the graphene self-assembled porous carbon material in this embodiment is 2376m 2 / g, specific capacitance 324F / g at current density of 0.05A / g.

[0093] Example 5

[0094] The preparation method of aromatic hydrocarbon synthesized graphene self-assembled porous carbon material is as follows:

[0095] 1. Add 1.4g silica aerogel and 40ml dichloromethane into a flask and stir evenly under nitrogen atmosphere;

[0096] 2. Add 6 g of naphthalene and stir evenly, then add 5.2 g of sodium chloride, stir and mix at 60° C. for 1 h, then add 4 g of ferric chloride and react for 1 h, then add 3.5 g of ferric chloride and react for 4 h, filter; dry at 120° C. for 3 h to obtain a graphene self-assembly precursor material;

[0097] 3. Place 1 g of the above graphene self-assembly precursor material in a tubular furnace, heat it to 500°C at 10°C / min under a nitrogen atmosphere and carbonize it for 1 hour; take it out and mix it with 3 g of KOH, place it at 800°C for carbonization for 1 hour, wash the carbonized product with water, ultrasonically treat it, and dry it to obtain a graphene self-assembled porous carbon material.

[0098] After testing, the specific surface area of ​​the graphene self-assembled porous carbon material in this embodiment is 2421m 2 / g, specific capacitance 302F / g at current density of 0.05A / g.

[0099] Example 6

[0100] The preparation method of aromatic hydrocarbon synthesized graphene self-assembled porous carbon material is as follows:

[0101] 1. Add 1.4g silica aerogel and 40ml dichloromethane into a flask and stir evenly under nitrogen atmosphere;

[0102] 2. Add 6 g of naphthalene, stir evenly, then add 6 g of aluminum chloride, react at 60 ° C for 1 hour, then add 6.5 g of trimethylaluminum to react for 5 hours, filter; dry at 120 ° C for 3 hours to obtain a graphene self-assembly precursor material;

[0103] 3. Place 1 g of the above graphene self-assembly precursor material in a tubular furnace, heat it to 500 °C at 10 °C / min under a nitrogen atmosphere and carbonize it for 1 h; take it out and mix it with 3 g of KOH, place it at 850 °C for 1 h, wash the carbonized product with water, ultrasonically treat it, and dry it to obtain a graphene self-assembled porous carbon material.

[0104] After testing, the specific surface area of ​​the graphene self-assembled porous carbon material in this embodiment is 2076m 2 / g, and the specific capacitance is 274F / g at a current density of 0.05A / g.

[0105] Example 7

[0106] The preparation method of aromatic hydrocarbon synthesized graphene self-assembled porous carbon material is as follows:

[0107] 1. Add 1.4g silica aerogel and 40ml dichloromethane into a flask and stir evenly under nitrogen atmosphere;

[0108] 2. Add 2.8 g of naphthalene, stir evenly, then add 2.8 g of aluminum chloride, react at 60 ° C for 1 hour, then add 3.5 g of ferric chloride to react for 5 hours, filter; dry at 120 ° C for 3 hours to obtain a graphene self-assembly precursor material;

[0109] 3. Place 1 g of the above graphene self-assembly precursor material in a tubular furnace, heat it to 500 °C at 10 °C / min under a nitrogen atmosphere and carbonize it for 1 h; take it out and mix it with 3 g of KOH, place it at 850 °C for 1 h, wash the carbonized product with water, ultrasonically treat it, and dry it to obtain a graphene self-assembled porous carbon material.

[0110] After testing, the specific surface area of ​​the graphene self-assembled porous carbon material in this embodiment is 2506m 2 / g, specific capacitance 353F / g at current density of 0.05A / g.

[0111] The embodiments of the present invention have been described above, and the above description is exemplary, not exhaustive, and is not limited to the disclosed embodiments. Many modifications and changes will be apparent to those skilled in the art without departing from the scope and spirit of the described embodiments.

Claims

1. A method for preparing a porous carbon material synthesized from aromatic graphene, characterized in that: The preparation method comprises: (1) in the presence of a protective gas, a solvent, a catalyst and an optional molten salt, using a silica aerogel as a template and an aromatic hydrocarbon as a reaction monomer to react to obtain a graphene self-assembly precursor material; (2) Carbonizing the graphene self-assembly precursor material to obtain the aromatic hydrocarbon synthesized graphene self-assembly porous carbon material.

2. The preparation method according to claim 1, wherein The catalyst is added in steps, wherein a portion of the catalyst is added first, reacts for a period of time, and then another portion of the catalyst is added to continue the reaction; Preferably, relative to 1 mol of aromatic hydrocarbon, the amount of the catalyst added is 0.25 to 2 mol, preferably 0.5 to 1 mol, and the amount of the other catalyst added is 0.25 to 2 mol, preferably 0.5 to 1 mol; Preferably, the reaction time is 1-2 hours, and the reaction time is 1 to 9 hours.

3. The preparation method according to claim 1, wherein The aromatic hydrocarbon is a condensed ring aromatic hydrocarbon, and preferably includes at least one of naphthalene, biphenylene, methylnaphthalene, phenanthrene, pyrene, fluorene, anthracene, indene, benzopyrene, azulene, tetracene, pentacene, triacene, hexacene and heptabenzocyclopentadiene.

4. The preparation method according to claim 1, wherein The catalyst is a Lewis acid, preferably at least one of aluminum chloride, trimethylaluminum, aluminum bromide, ferric chloride, boron trichloride, antimony chloride, cupric chloride, cuprous iodide, cuprous bromide, boron trifluoride, tin tetrachloride, titanium tetrachloride and silver trifluoromethanesulfonate; The molten salt includes at least one of sodium chloride, sodium nitrate, sodium sulfate, barium chloride, calcium chloride, calcium sulfate, copper chloride, potassium chloride, potassium sulfate and potassium nitrate; The solvent includes at least one of dichloroethane, dichloromethane, chloroform, carbon tetrachloride, ethyl acetate and xylene; The protective gas is nitrogen.

5. The preparation method according to claim 1, wherein In step (1), the mass ratio of the silica aerogel to the aromatic hydrocarbon is 1:(2-5); The molar ratio of the aromatic hydrocarbon to the catalyst is 1:(0.5-4), preferably 1:(1-2); The molar ratio of the molten salt to the aromatic hydrocarbon is (0-3):1, preferably (1.5-2):1; The reaction temperature is 30-100°C.

6. The preparation method according to claim 1, wherein In step (2), the carbonization treatment is to heat the graphene self-assembly precursor material to 300-600° C. in a nitrogen atmosphere for carbonization for 1-3 hours, then mix it with an activator, and carbonize it at 600-900° C. for 1-5 hours to obtain a carbonized product; Preferably, after the carbonization treatment, the carbonization product is washed with water, ultrasonically treated and dried to obtain the aromatic hydrocarbon synthesized graphene self-assembled porous carbon material; Preferably, the mass ratio of the graphene self-assembly precursor material to the activator is 1:(1-3).

7. Aromatic hydrocarbon synthesized graphene self-assembled porous carbon material prepared according to the preparation method according to any one of claims 1 to 6.

8. The porous carbon material according to claim 7, wherein The aromatic hydrocarbon synthesized graphene self-assembled porous carbon material has a three-dimensional network structure.

9. The porous carbon material according to claim 7, wherein The specific surface area of ​​the aromatic hydrocarbon synthesized graphene self-assembled porous carbon material is 1500m 2 / g~2600m 2 / g, and the specific capacitance is 165F / g~353F / g at a current density of 0.05A / g.

10. Use of the aromatic hydrocarbon synthesized graphene self-assembled porous carbon material as claimed in any one of claims 7 to 9 as a supercapacitor electrode material.

Citation Information

Patent Citations

  • Porous graphite-phase carbon nitride nanomaterial, and synthesis method and application thereof

    CN111841607A

  • Preparation method of nitrogen, phosphorus and oxygen co-doped porous graphitized carbon nanosheet

    CN112479199A

  • Graphene nanobelt and preparation method thereof

    CN114735680A

  • Method for preparing high performance nanoporous graphene foams with versatile usages

    KR1020180056099A

Cited By

  • Self-assembly macroscopic preparation method of low-carbon defective graphene in hot melting state and prepared low-carbon defective graphene

    CN120246998A